2009
DOI: 10.5194/angeo-27-2053-2009
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of pre-reversal enhancement of the zonal equatorial electric field

Abstract: Abstract.In November 2004, a large and variable interplanetary electric field (IEF) was felt in the reference frame of the Earth. This electric field penetrated to the magnetic equator and, when the Jicamarca Radio Observatory (JRO) was in the dusk sector, resulted in a reversal of the normal zonal component of the field. In turn, this caused a counter-electrojet (CEJ), a westward current rather than the usual eastward current. At the time of the normal pre-reversal enhancement (PRE) of the eastward field, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 8 publications
1
32
1
Order By: Relevance
“…Unfortunately, their earliest calculation was at 17:00 LT since they were studying the prereversal enhancement in the zonal electric field [Kelley et al, 2009]. Nonetheless, they found that the vertical electric field peaked at 107 km without needing to modify the collision frequency.…”
Section: A Classical Resolution To the Eej Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, their earliest calculation was at 17:00 LT since they were studying the prereversal enhancement in the zonal electric field [Kelley et al, 2009]. Nonetheless, they found that the vertical electric field peaked at 107 km without needing to modify the collision frequency.…”
Section: A Classical Resolution To the Eej Problemmentioning
confidence: 99%
“…Since E f is taken as the typical quiet time zonal electric field at noon on the basis of Jicamarca radar measurements [Kelley et al, 2009], it is possible to calculate E L by using the field line-integrated conductivities (equations (3) to (5)) together with the vertical current density (equation (8)) in equation (6). Note that we arbitrarily take t = 0 at local (solar time) noon.…”
Section: A Classical Resolution To the Eej Problemmentioning
confidence: 99%
“…whether it is due to the F-region dynamo electric fields getting freed from the field line E-region loading effect (Farley et al, 1986) or due to the irrotational nature of the electric field at the sunset terminator manifesting itself as an enhanced zonal wind (Rishbeth, 1981) or due to the evening EEJ (Haerendel and Eccles, 1992) is still not fully understood. Recently, Kelley et al (2009) considered the above three competing mechanisms that exist for the PRE, in the light of the penetration of a large electric field of interplanetary origin. Their study suggests that the normal PRE must be created by the Haerendel and Eccles (1992) mechanism, in which the EEJ partially closes in the post sunset F-region, and that the other two mechanisms are secondary.…”
Section: Introductionmentioning
confidence: 99%
“…It can be guessed a double peak structure in the hmF2 near noontime following the IEA and better shown at low solar activity. Also interesting is the observed highest altitudes region at the end of the anomaly, after sunset in the equatorial regions which correlates with the pre-reversal enhancement (PRE) phenomenon (Kelley et al, 2009).…”
Section: Pre-processing Considerations On the Database And The Time Pmentioning
confidence: 96%